Expression of the high-affinity purine nucleobase transporter in mutant mouse S49 cells does not require a functional wild-type nucleoside-nucleobase transporter. - Ullman, B (1987)
A novel type of somatic mutation that causes the expression of a high-affinity purine base permease (B. Aronow, D. Toll, J. Patrick, P. Hollingsworth, K. McCartan, and B. Ullmann, Mol. Cell Biol. 6:2957-2962, 1986) has been inserted into nucleoside transport-deficient S49 cells. Two classes of mutants expressing this nucleobase permease were generated. The first, as exemplified by the AE1HADPAB2 cell line, possessed an augmented capacity to transport low concentrations of the three purine bases, hypoxanthine, guanine, and adenine. The second class of mutants, as typified by the AE1HADPAB5 clone, possessed an augmented capability to translocate low levels of hypoxanthine and guanine, but not adenine. Neither the AE1HADPAB2 nor the AE1HADPAB5 cells could transport nucleosides, suggesting that the expression of the high-affinity base transporter did not reverse the mutation in the nucleoside transport system. The transport of purine bases by both AE1HADPAB2 and AE1HADPAB5 cells was much less sensitive than that by wild-type cells to inhibition by dipyridamole, 4-nitrobenzylthionosine, and N-ethylmaleimide, potent inhibitors of nucleoside and nucleobase transport in wild-type S49 cells. Fusion of the AE1HADPAB2 and AE1HADPAB5 cell lines with wild-type cells indicated that the expression of the high-affinity base transporter behaved in a dominant fashion, while the nucleoside transport deficiency was a recessive trait. These data suggest that the high-affinity purine base transporter of mutant cells and the nucleoside transport function of wild-type cells are products of different genes and that expression of the former probably requires the unmasking or alteration of a specific genetic locus that is silent or different in wild-type cells.